Government debt levels and the systemic risks associated with post-crisis fiscal policies - Koekemoer, Jonathan (Rhodes University, Faculty of Commerce, Department of Economics, 2013)
The study analyses the concepts of intergenerational equity and fiscal sustainability in South Africa. The question raised is whether or not South Africa can adopt stimulatory fiscal measures, with a simultaneous increase in debt, so as to improve long-term growth potential in a sustainable manner without creating an excessive burden on future generations. The debate surrounding the use of stimulatory fiscal policy has come to the fore once again as monetary policy has become a restricted and ineffective macroeconomic policy tool in certain countries after the world-wide financial crisis and the Euro-debt crisis. Fiscal sustainability risks and high debt levels remain a source of concern in the United States and the Euro-zone, while South Africa presently seems to be at no great risk. With South Africa's intention to become a developmental state, the use and appropriateness of fiscal policy is considered. An overlapping-generations model is used to determine whether or not future generations will be burdened due to current stimulatory policy. The use of fiscal rules in South Africa is discussed and considered in light of various political incentives and constraints. The conclusion given is that the possible use of a procedural fiscal rule, such as the 'golden rule', may add credibility to the current regime, while a numerical fiscal rule is seen as unnecessary given South Africa's responsible use of fiscal policy thus far. As it stands, there is little possibility or risk that the public debt in South Africa will become too high in the near future. Although South Africa has been affected by the crisis, the developmental nature of the economy has been sustained through the use of responsible discretionary fiscal policy, putting South Africa in a positive position to meet its long-run growth potential.
Keywords: Finance, Public; Debts, Public -- South Africa; Fiscal policy; Monetary policy -- South Africa